2006
DOI: 10.1093/intqhc/mzl026
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of discharge management for geriatric patients at risk of readmission or institutionalization

Abstract: This implementation project showed that a discharge planning intervention can reduce institutionalization rates of elderly patients in real-life settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 19 publications
0
25
0
10
Order By: Relevance
“…33 In a review of 12 trials involving general medical patients, no effects were seen on readmissions; 34 similar results were seen in two other trials that recruited a total of 3557 patients. 35,36 Collaboration with primary care and general practitioners in discharge processes…”
Section: Discharge Coordinatorsmentioning
confidence: 99%
“…33 In a review of 12 trials involving general medical patients, no effects were seen on readmissions; 34 similar results were seen in two other trials that recruited a total of 3557 patients. 35,36 Collaboration with primary care and general practitioners in discharge processes…”
Section: Discharge Coordinatorsmentioning
confidence: 99%
“…The researchers reported that the patients assigned to the usual care group had nearly double the readmission rate by 15 days post-discharge, but the number of readmissions between 15 and 90 days was not significantly different among the groups (Steeman et al, 2006).…”
Section: Telemedicine and Ehealthmentioning
confidence: 99%
“…The researchers found reduced readmission rates within 30 days of the patients who received the TCM program 12.66%, as compared to 35.85% for the group that received no intervention (Ahmed &Rak, 2010). Discharge management by trained social workers or nurses may result in fewer elderly patients being institutionalized in a nursing home in the first days after hospital discharge (Steeman, Moons, Milisen, de Bal, de Geest, de Froidmont, Tellier, Gossett & Abraham, 2006). A quasi-experimental study was done to evaluate whether the application of "discharge management" reduced hospital readmissions and institutionalization of geriatric patients.…”
Section: Telemedicine and Ehealthmentioning
confidence: 99%
See 1 more Smart Citation
“…tudios que muestran cómo la gestión de casos influye en la reducción de institucionalizaciones en pacientes geriá-tricos (30), o sobre su influencia en las disminuciones significativas en la hospitalización (31), o su capacidad preventiva para evitar la re-hospitalización (29,32). También tenemos evidencias sobre la influencia de la misma sobre la disminución de costes (33)(34)(35), aunque eso será analizado posteriormente.…”
Section: Influencia De Las Enfermeras Gestoras De Casos Hospitalariasunclassified